LEKSIKON ETNOMEDISIN DALAM PENGOBATAN TRADISIONAL SUKU DAYAK BAKUMPAI - NFN Hestiyana (Balai Bahasa Kalimantan Barat, 2019)
This research is based on the conception of the Dayak Bakumpai tribe towards traditional medicine. This study analyzed ethnomedical lexicons in traditional Dayak Bakumpai tribal medicine. The purpose of this study is to describe the ethnomedicin lexicon and the techniques of composition in the traditional treatment of the Dayak Bakumpai tribe. The method used in this study is qualitative descriptive method. The data in this study were ethnomedicin lexicons in traditional medicine and the techniques of composition in traditional medicine of the Dayak Bakumpai tribe obtained from informants in Barito Kuala Regency, South Kalimantan. Data collection techniques used are the method of referencing, note taking, and library research. The instrument of this study was the researcher as observer and observation sheets. Data analysis includes the classification of ethnomedicin lexicon based on the types of medicinal plants and their functions and the techniques of composition in the traditional treatment of the Dayak Bakumpai tribe. Then, describe, analyze, transcribe, interpret, and conclude the results of the study. From the results of the ethnomedicin lexicon analysis in traditional Dayak Bakumpai tribal medicine, 40 ethnomedicin lexicons were found in traditional Dayak Bakumpai tribal medicine based on the types of medicinal plants and their functions. Then, plant parts are used for medicine, namely roots, tubers (rhizomes), stems, leaves, shoots, and parts of plant skin. Furthermore, the techniques of composition in the traditional treatment of the Dayak Bakumpai tribe are carried out by drinking, smearing, rubbing, sticking, evaporating, and watering to the body part (bathing).